Ethnic Differences in Perceptions of Cognitive Ability Tests: The explanatory role of self‐serving attributions. (March 2016) - Oostrom, Janneke K.; De Soete, Britt
Abstract : This study examined the role of self‐serving attributions in the formation of pretest and posttest fairness perceptions of cognitive ability tests among ethnic majority and ethnic minority applicants. In total, 180 unemployed (52.8% Dutch majority) job seekers participated in an application training program consisting of a cognitive ability test and several pretest and posttest questionnaires. Results showed that both pretest and posttest fairness perceptions are prone to self‐serving attributions. Ethnic minority applicants have a stronger tendency than ethnic majority applicants to attribute their previous test experiences and their perceived test performance to the fairness of cognitive ability testing. Self‐serving attributions were partly explained by (ethnic differences in) attribution style.